Creative Geographies: experiential affinities in art-geography relations - Souza Júnior,Carlos Roberto Bernardes de (2020)
Abstract Characterized by reciprocal influences with artistic practices, creative geographies intend to explore innovative methodologies in Cultural Geography’s field. The essay has the objective of unraveling the ways by which the creative (re)turn in Geography can potentialize research practices for the contemporary geographer. To do so, bibliographical research and revision were employed alongside an approach with Merleau-Ponty’s existentialist phenomenology philosophical provocations. It has comprehended that the different ways of making and writing Geography in the context of its creative turn can bring new reaches to its study field. Innovations on research divulgation and ways of approaching subjects/objects are an important motivation for possibilities in the development of geographical science. Creative geographies are more than a passing tendency and can be a foundational route for contemporary Cultural Geography innovations.